Exploring primary school mathematics teachers use of gamification in formative assessment: a case study - Simelane, Thando (Rhodes University, Faculty of Education, Department of Education)
Technology integration has gained much influence with the emergence of technological tools in educational areas. The vast resources and opportunities that technologies and the Internet have brought new approaches, strategies, and tools to assess learners' performance in many subject areas. Teachers have many computer/mobile device applications and learning management systems. Most teachers are trying new ways of integrating technology into the mathematics classroom to increase the quality of teaching and learning. Thus, this study explored how primary school mathematics teachers use Kahoot as a formative assessment tool. The study adopted an exploratory case study underpinned by the interpretive paradigm. It was conducted in a primary school in the Shiselweni Region in Swaziland. The participants were ten mathematics teachers teaching different grades at the school. Data was generated using observations, workshops, structured questionnaires, journal reflections and focus group interviews. The theoretical and analytical framework that underpinned this study was a combination of Davis' (1989) Technology Acceptance Model (TAM) and Mishra & Koehler's (2006) Technological Pedagogical Content Knowledge (TPACK) framework. The study results showed that the perceptions and attitudes of primary school mathematics teachers towards using Kahoot generally appear to be positive. The study also revealed that all the participants found Kahoot helpful and perceived it as easy to use. The study found that the provision of technical support for teachers; and financial support for schools to implement technology use in the classroom were enabling factors for using Kahoot as a formative assessment technology. Constraining factors were lack of high-speed internet connectivity; and lack of basic technological knowledge for using Kahoot in formative assessment. The study concluded that Kahoot increases learner motivation, engagement, attention, enjoyment, and knowledge retention. This study recommended the integration of Kahoot gamification into the mathematics curriculum.The study recommends that there is a need for schools to initiate the presence of technologies in mathematics classrooms and encourage teachers to integrate technologies assessment and teaching. The study suggest future research to explore use of Kahoot as a formative assessment technology in resource-constrained schooling contexts using multiple cases.
Keywords: Kahoot!; Gamification; Technological Pedagogical Content Knowledge; Mathematics-- Study and teaching (Elementary) Eswatini Shiselweni; Educational technology; Formative assessment